Evolution of eggshell structure in relation to nesting ecology in non‐avian reptiles. (14th April 2021) - D'Alba, Liliana; Goldenberg, Jonathan; Nallapaneni, Asritha; Parkinson, Dilworth Y.; Zhu, Chenhui; Vanthournout, Bram; Shawkey, Matthew D.
Abstract: Amniotic eggs are multifunctional structures that enabled early tetrapods to colonize the land millions of years ago, and are now the reproductive mode of over 70% of all terrestrial amniotes. Eggshell morphology is at the core of animal survival, mediating the interactions between embryos and their environment, and has evolved into a massive diversity of forms and functions in modern reptiles. These functions are critical to embryonic survival and may serve as models for new antimicrobial and/or breathable membranes. However, we still lack critical data on the basic structural and functional properties of eggs, particularly of reptiles. Here, we first characterized egg shape, shell thickness, porosity, and mineralization of eggs from 91 reptile species using optical images, scanning electron microscopy, and micro computed tomography, and collected data on nesting ecology from the literature. We then used comparative analyses to test hypotheses on the selective pressures driving their evolution. We hypothesized that eggshell morphology has evolved to protect shells from physical damage and desiccation, and, in support, found a positive relationship between thickness and precipitation, and a negative relationship between porosity and temperature. Although mineralization varied extensively, it was not correlated with nesting ecology variables. Ancestral state reconstructions show thinning and increased porosity over evolutionary time in squamates, but the opposite in turtles and crocodilians. Egg shape, size, porosity and calcification were correlated, suggesting potential structural or developmental tradeoffs. This study provides new data and insights into the morphology and evolution of reptile eggs, and raises numerous questions for additional research. Abstract : Reptile eggs have changed over evolutionary time, spherical eggs arose independently in turtles and geckos. Shells have become thinner and more porous in squamate reptiles, but thicker in testudines and crocodilians. Eggshell thickness and porosity have evolved in relation to environmental factors and nest type.